Bionic surface diode for droplet steering. Issue 2 (9th February 2023) - Yang, Xiaolong; Qi, Biao; Lu, Yao; Zhang, Wang; Wang, Xiaolei
Abstract: Control of droplet sliding and its interfacial behavior such as sliding resistance and friction have important applications in microfluidic and energy‐related fields. Nature provides many examples of interface‐driven droplet sliding control; yet, to date, the continuous governing of the multiphase process and precise steering of droplet sliding remain challenging. Here, directional‐dependent ultraslippery patterned surfaces with significant droplet sliding anisotropy were created by coordinating the heterogeneous wettability of the back of the dessert beetle, directional‐dependent architecture of the butterfly wing, and ultraslippery configuration of the Nepenthes alata . Analysis of the sliding resistance on typical ultraslippery patterned surfaces reveals that the directional‐dependent triple phase line (TPL) immigration on the ultraslippery patterns dominates the strong sliding anisotropy, which can be modeled using the classic Furmidge equation. In particular, the sliding anisotropy for the semicircular ultraslippery patterned surface shows threefold higher than that of natural butterfly wings due to the most significant difference in TPL immigration in two opposite directions, which enables the simultaneous handling of multiple droplets without mass loss and steering of droplet sliding/friction. This work may transform the design space for the control of multiphase interface motion and the development of new lab‐on‐a‐chip and droplet‐based microsystems. Abstract : We report multi‐bioinspired slippery lubricant‐infused porous surface (SLIPS)‐patterned superamphiphobic surfaces, which enable simultaneous handling of multiple droplets without mass loss and precise steering of droplet friction by carefully architecting the SLIPS patterns. This work may provide enlightenment on the creation of diode structures with excellent sliding anisotropy that serve as both a high‐throughput bioassay platform for handling reagent droplet arrays and droplet‐based mini parts for transferring the energy in microscales.